An overview of water reallocation and the barriers to its implementation. (24th May 2016) - Marston, Landon; Cai, Ximing
Abstract : The growing number of areas facing water scarcity necessitates adaptive water management strategies beyond traditional water supply and demand management methods, which are becoming increasingly difficult in many regions. Water reallocation offers a flexible water management approach to mitigate water scarcity under changing socioeconomic, climatic, and environmental conditions. In spite of the numerous benefits of reallocating water between users, examples of successful water transfers are relatively sparse and the expected benefits are rarely met in full due to several complex impediments. This study overviews the current body of water reallocation literature, with a particular focus on the key barriers to wider implementation of water reallocation. We argue that to overcome these obstacles a more interdisciplinary approach to water reallocation should be advanced that couples developments in the natural sciences and engineering disciplines with current water reallocation scholarship, which is predominately rooted in the social sciences. Many examples of water transfers from around the world are used to illustrate both the benefits and challenges associated with reallocation, as well as to identify measures to overcome some of the major difficulties. We conclude by calling for an integrated research platform that focuses on supporting both voluntary and nonvoluntary forms of water reallocation; however, a greater emphasis should be on nonmarket means of water transfer since it is more feasible for many regions where water rights are not well defined and institutional capacity is insufficient. WIREs Water 2016, 3:658–677. doi: 10.1002/wat2.1159 This article is categorized under: Engineering Water > Planning Water Human Water > Water Governance Human Water > Water as Imagined and Represented